2006
DOI: 10.1021/jp062178z
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Decomposition on Small Rhodium Clusters, Rhn+/-

Abstract: The decomposition of nitric oxide on small charged rhodium clusters Rh(n)(+/-) (6 < n < 30) has been investigated by Fourier transform ion cyclotron resonance mass spectrometry. For both cationic and anionic naked clusters, the rates of reaction with NO increase smoothly with cluster size in the range studied without the dramatic size-dependent fluctuations often associated with the reactions of transition-metal clusters. The cationic clusters react significantly faster than the anions and both exhibit rate co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
137
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(142 citation statements)
references
References 65 publications
5
137
0
Order By: Relevance
“…In their Fourier transform ion cyclotron resonance studies of reactions of NO with Rh + 6 , Ford et al 30 observed biexponential kinetics, which they have interpreted in terms of structural isomerism. In another experimental study of NO decomposition on small, charged Rh clusters, Anderson et al 31 have reported that, for both cationic and anionic clusters, the reaction rate increases smoothly with cluster size, though the reaction proceeds significantly faster on cationic clusters than on anionic ones. Motivated by these experimental studies, Harding et al 27 have performed DFT studies of NO adsorption and dissociation on structural and spin isomers of Rh + 6 .…”
Section: Previous Work On Rhn and No-rhnmentioning
confidence: 99%
“…In their Fourier transform ion cyclotron resonance studies of reactions of NO with Rh + 6 , Ford et al 30 observed biexponential kinetics, which they have interpreted in terms of structural isomerism. In another experimental study of NO decomposition on small, charged Rh clusters, Anderson et al 31 have reported that, for both cationic and anionic clusters, the reaction rate increases smoothly with cluster size, though the reaction proceeds significantly faster on cationic clusters than on anionic ones. Motivated by these experimental studies, Harding et al 27 have performed DFT studies of NO adsorption and dissociation on structural and spin isomers of Rh + 6 .…”
Section: Previous Work On Rhn and No-rhnmentioning
confidence: 99%
“…Their use is advantageous for understanding the behavior of N and O atoms at the atomic and molecular level, since the number of Rh, N, and O atoms involved in the reaction is well defined. [6][7][8][9][10][11] For instance, Mackenzie et al investigated the reduction of NO on rhodium clusters by single collision reactivity experiments performed by Fourier transform mass spectrometry in the gas phase. The experiments suggested that the first NO molecule predominantly adsorbs dissociatively on Rhn + clusters (n < 17).…”
Section: Introductionmentioning
confidence: 99%
“…For Rh6 + , four NO molecules can be reduced yielding N2 before the remaining oxygen atoms disrupt NO reduction; further NO molecules only adsorb onto Rh6O4 + clusters. [6][7][8][9] Harding et al calculated the geometrical structures of stable Rh6O1-4 + clusters and studied the adsorption form of NO on Rh6O4 + using density functional theory (DFT). 12,13 The calculations suggest that stable clusters have an octahedral tetragonal bipyramidal (octahedral) or capped-square pyramidal structure.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic moments, 4,5 electric polarizability, 6 and reactivity with a range of small molecules [7][8][9][10][11][12][13][14][15][16] have been investigated, in many instances revealing a significant size dependence of these properties. In several cases, reaction rate measurements on monodisperse cluster samples have suggested multiple reactivities, indicating the presence of multiple forms of clusters of the same size.…”
Section: Introductionmentioning
confidence: 99%